2008
DOI: 10.1002/ange.200705989
|View full text |Cite
|
Sign up to set email alerts
|

Color Change of Proteorhodopsin by a Single Amino Acid Replacement at a Distant Cytoplasmic Loop

Abstract: Rot mutiert zu Rosa: Während bisher angenommen wurde, dass nur die Aminosäuren nahe des Retinalchromophors maßgeblich für die Farbabstufung durch Rhodopsine sind, wurde nun gefunden, dass beim Proteorhodopsin, einem Archaea‐Rhodopsin aus Meeresbakterien, eine Farbänderung aus der Mutation von Ala178 zu Arg in der E‐F‐Schleife resultiert. Die Rotverschiebung beträgt im neutralen pH‐Bereich ungefähr 20 nm (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 32 publications
1
42
2
Order By: Relevance
“…Kandori and co-workers (14) have shown that a single mutation A178R in the EF loop of GPR, which is far away from the retinal binding site, causes a surprisingly large redshift and changes the pK a of the primary proton acceptor D97 (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Kandori and co-workers (14) have shown that a single mutation A178R in the EF loop of GPR, which is far away from the retinal binding site, causes a surprisingly large redshift and changes the pK a of the primary proton acceptor D97 (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
“…For example, one single point mutation L105Q in GPR, which is close to the chromophore, shifts the absorption maximum toward blue, whereas the corresponding Q105L mutation in blue absorbing PR causes a green shift (6,13). The recent discovery of a 20 nm redshift of the GPR absorption spectrum upon a single mutation A178R in the EF loop came therefore as a great surprise as the mutation site is far away from the retinylidene (14). This effect is highly position specific and has not been observed in BR (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that these amino acid residues also affect protein folding functions and stability [27]. Ala178 in the distant cytoplasmic loop (E–F loop) affects the colour change of PR [28]. In addition, research on red‐shifted rhodopsin has been performed via a machine learning‐based experimental design method [29,30].…”
mentioning
confidence: 99%
“…It is also possible that the amino acid replacement may have caused broader structural changes to the protein. In the case of proteorhodopsin, the replacement of A178, an amino acid located in the EF loop, with arginine caused large changes to absorption spectrum and photocycle of it . These changes include 20 nm redshift of the absorption maximum of the ground state, elevated pKa of the primary proton acceptor, a faster decay of K and M intermediates, 10 times elongation of the photocycle, and chromophore configurational change.…”
Section: Discussionmentioning
confidence: 99%